IMPLEMENTASI PENDIDIKAN KARAKTER QUR’ANI (Studi Analisis Deskriptif di Pondok Pesantren Al-Qur’aniyah Tangerang Selatan) - Neneng Sakinah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
This research is motivated by the moral decadence which endanger and become the focus in education sector in Indonesia. But, in reality the education institution has not been success yet as the role and functional strategy in create the human that have a certain character and cultured based on the religious norm and Pancasila. This research uses the qualitative method with descriptive analysis. The result show that Al-Qur’aniyah boarding school implements and develops concept and value of Qur’anic character education such as tauhid, iman and takwa through kajian and learning process in the class, extracuriculer, the culture of the boarding school dan citizen based. The implementation of character Qur’anic education influenced by student’s motivation, the role of teacher, ustadz, kyai, environment, parents, facility and society. The strategy that implemented this character education here is do’a, exemplary, habituation, advice, musabaqoh, and reward and punishment. The result show that the implementation of character Qur’anic boarding education at Al-Qur’aniyah boarding school is succeed based on the score of akhlak in the raaport, parents’s testimonial which feel satisfied with the improvement in academic and nonacademic of their children especially in Qur’anic knowledge.